Complaints Information System for the Polytechnic of South Aceh - IHSAN, ARINAL; Ben, Hasbaini; Fardiansyah; Putra, D.S; Asmaidi (LPPM Politeknik Aceh Selatan, 2021)
The industrial revolution 4.0 is a hot topic discussed only among academics and industry. Of course, this condition is a positive thing that shows that people have started to care about utilizing technology that is developing very rapidly today. South Aceh Polytechnic (POLTAS) as a vocational higher education institution, of course, must be consistent in making innovations in improving services to stakeholders. The quality and quality of service to stakeholders must of course be maintained so that input, criticism, and suggestions from them are one of the most important factors in creating a safe and comfortable academic atmosphere for higher education, especially POLTAS. The formulation of the problem in this study is how to build and simulate the results of an information system that can adapt dynamically in carrying out the political services of South Aceh provided to stakeholders. The purpose of this research is to build a Complaints Information System for the Polytechnic of South Aceh (SIAPA). This research is also part of the POLTAS Internal Quality Assurance System (SPMI) which is managed independently assigns to control and improve quality in the implementation of higher education in a planned manner (with designed) and sustainable (sustainable). This type of research is applied research with case studies at the South Aceh Polytechnic. The research procedure is in several stages, namely planning, analysis, design, development, testing, implementation, simulation of results, and evaluation.